Effects of xylitol chewing gum and candies on the accumulation of dental plaque: a systematic review - Söderling Eva; Pienihäkkinen Kaisu (SPRINGER HEIDELBERG, 2022)
Objectives A systematic review of published data was conducted with the aim of assessing the effects of xylitol consumption on the amount of dental plaque.
Materials and methods Electronic and hand searches were performed to find clinical studies concerning the effects of xylitol chewing gum or candies on dental plaque. Prospective randomized controlled clinical trials published between 1971 and 2020 conducted in healthy subjects were included in the review.
Results The initial search identified 424 xylitol articles. After applying inclusion and exclusion criteria, altogether 14 articles (16 studies) were reviewed. The review identified 12 of the total of 14 xylitol chewing gum studies as having fair or high quality. In 13 of the 14 chewing gum studies, xylitol gum decreased plaque accumulation. In six studies, xylitol gum chewing decreased plaque compared to sorbitol gum, and in three studies compared to gum base/no gum. In three fair-quality studies conducted with xylitol candies, plaque accumulation did not change.
Conclusions Habitual xylitol gum chewing appears to show plaque-reducing effects that differ from those of sorbitol gum. This suggests specific effects for xylitol on plaque accumulation. Xylitol candies appear not to decrease plaque. The heterogeneity of the studies warrants further research.